Effect of contact media on the diagnostic quality of electrical resistance measurements for occlusal caries - Mosahebi N, Ricketts DNJ. (Blackwell Synergy, 2002)
Electrical resistance measurements have been used for the diagnosis of occlusal caries. Both site and surface-specific techniques have been described, the latter more suited to clinical trials or epidemiological surveys. For surface-specific measurements the tooth is dried and a contact medium drawn along the fissure pattern to provide an electrical contact between a probe tip and the tooth surface.